Light In The Darkness : African Americans and the YMCA, 1852-1946 - Mjagkij, Nina, 1961- (Book collections on Project MUSE., 1994)
From the time of its emergence in the United States in 1852, the Young Men's Christian Association excluded blacks from membership in white branches but encouraged them to form their own associations and to join the Christian brotherhood on ""separate but equal"" terms. Nina Mjagkij's book, the first comprehensive study of African Americans in the YMCA, is a compelling account of hope and success in the face of adversity. African American men, faced with emasculation through lynchings, disenfranchisement, race riots, and Jim Crow laws, hoped that separate YMCAs would provide the opportunity to.